2019
DOI: 10.1080/13561820.2019.1586658
|View full text |Cite
|
Sign up to set email alerts
|

Framing IPE. Exploring meanings of interprofessional education within an academic health professions institution

Abstract: This paper reports a qualitative study that explored the meanings of interprofessional education (IPE) by comparing and contrasting educational leaders' perceptions with educational policy documents at an academic health professions education institution in Scandinavia. The study used Goffman's frame analysis to identify two frames of IPE by illuminating issues related to the definition, rationale, and presentation of IPE. A directed content analysis to identify these three aspects of IPE was conducted on semi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
0
6
0
2
Order By: Relevance
“…First, IPE needs to be standardized across teaching and learning, specifically in wound care contexts. As yet, IPE is not well understood; thus, programs face potential difficulties in its implementation, especially when exploring the meanings of IPE within an academic health professional institution, as discussed by Sundberg et al 32 In their Framework for Action on IPE and Collaborative Practice (2010), the World Health Organization indicated that it is necessary to agree on a common vision and purpose for IPE that includes all stakeholders across faculties and organizations 1 . In the present study, the researchers found it was necessary to educate facilitators on standardized definitions used within IPE, to ensure consistency and competence in the delivery of education and expertise in accordance with the recognized international IPE vision 1 .…”
Section: Discussionmentioning
confidence: 99%
“…First, IPE needs to be standardized across teaching and learning, specifically in wound care contexts. As yet, IPE is not well understood; thus, programs face potential difficulties in its implementation, especially when exploring the meanings of IPE within an academic health professional institution, as discussed by Sundberg et al 32 In their Framework for Action on IPE and Collaborative Practice (2010), the World Health Organization indicated that it is necessary to agree on a common vision and purpose for IPE that includes all stakeholders across faculties and organizations 1 . In the present study, the researchers found it was necessary to educate facilitators on standardized definitions used within IPE, to ensure consistency and competence in the delivery of education and expertise in accordance with the recognized international IPE vision 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Inter-professional education becomes a fundamental need in order to collaborate in environments of uncertainty. 40 This type of teaching and collaboration allows team members to make decisions as equals to ensure the quality and safety of clinical care. 41 Inter-professional intervention becomes an opportunity to find new strategies for the treatment of patients with COVID-19.…”
Section: Medical Schools New Social Function After the Pandemicmentioning
confidence: 99%
“…La educación interprofesional se convierte en una necesidad fundamental para colaborar en ambientes de incertidumbre. 40 Este tipo de enseñanza y colaboración permite a los integrantes del equipo tomar decisiones como iguales para asegurar la calidad y seguridad de la atención clínica. 41 La intervención interprofesional se convierte en una oportunidad para encontrar nuevas estrategias para el tratamiento de los pacientes con COVID-19.…”
Section: El Perfil Tradicional De Los Egresadosunclassified